Levels of innate immune factors in preterm and term mothers' breast milk during the 1st month postpartum. Issue 7 (19th February 2016) - Trend, Stephanie; Strunk, Tobias; Lloyd, Megan L.; Kok, Chooi Heen; Metcalfe, Jessica; Geddes, Donna T.; Lai, Ching Tat; Richmond, Peter; Doherty, Dorota A.; Simmer, Karen; Currie, Andrew
Abstract: There is a paucity of data on the effect of preterm birth on the immunological composition of breast milk throughout the different stages of lactation. We aimed to characterise the effects of preterm birth on the levels of immune factors in milk during the 1st month postpartum, to determine whether preterm milk is deficient in antimicrobial factors. Colostrum (days 2–5 postpartum), transitional milk (days 8–12) and mature milk (days 26–30) were collected from mothers of extremely preterm (<28 weeks of gestation, n 15), very preterm (28–<32 weeks of gestation, n 15), moderately preterm (32–<37 weeks of gestation, n 15) and term infants (37–41 weeks of gestation, n 15). Total protein, lactoferrin, secretory IgA, soluble CD14 receptor (sCD14), transforming growth factor- β 2 (TGF- β 2), α defensin 5 (HD5), β defensins 1 (HBD1) and 2, IL-6, IL-10, IL-13, interferon- γ, TNF- α and lysozyme (LZ) were quantified in milk. We examined the effects of lactation stage, gestational age, volume of milk expressed, mode of delivery, parity and maternal infection on milk immune factor concentrations using repeated-measures regression analysis. The concentrations of all factors except LZ and HD5 decreased over the 1st month postpartum. Extremely preterm mothers had significantly higher concentrations of HBD1 and TGF- β 2 in colostrum than term mothers did. After controlling for other variables in regression analyses, preterm birth was associated with higher concentrations of HBD1, LZ and sCD14 in milk samples. In conclusion, preterm breast milk contains significantly higher concentrations of some immune proteins than term breast milk.